Barriers and facilitators associated with steps of the HIV care cascade for migrants in OECD countries: a systematic mixed studies review protocol. Issue 11 (6th November 2020) - Arora, Anish; Quesnel-Vallee, Amelie; Lessard, David; Mate, Kedar; Rodriguez-Cruz, Adriana; Kronfli, Nadine; Engler, Kim; Vedel, Isabelle; Lebouché, Bertrand
Abstract : Introduction: In 2019, the United Nations signalled a substantial rise in the number of international migrants, up to 272 million globally, about half of which move to only 10 countries, including 8 member nations of the Organization for Economic Co-operation and Development (OECD). Migrants in OECD countries are often at higher risk for acquiring HIV and have a higher frequency of delayed HIV diagnosis. The barriers and facilitators that migrant people living with HIV (PLWH) in OECD countries face in relation to HIV care are insufficiently understood. The five-step HIV Care Cascade Continuum (HCCC) is an effective model to identify gaps, barriers and facilitators associated with HIV care. The purpose of this study is to generate a comprehensive, multilevel understanding of barriers and facilitators regarding the five steps of the HCCC model in OECD countries by migration status. Methods and analysis: A systematic mixed studies review using a data-based convergent design will be conducted. Medline, Embase, Scopus, CINAHL and the Cochrane Library will be searched on 25 March 2020. Screening and critical appraisal will be conducted independently by the first author. Authors 3–5 will act as second reviewers, each independently conducting 33% of the screening and appraisal. Quantitative data will be transformed to qualitative data and be synthesised using thematic analysis. The Mixed Methods Appraisal Tool will be used for quality assessment. An advisory committee, composed of four migrant PLWH, will be involved in screening and appraising 5% of articles to build knowledge and experience with systematic reviews. They will also be involved in analysis and dissemination. Ethics and dissemination: Ethics approval was obtained from the McGill University Health Centre (15-188-MUHC, 2016-1697, eReviews 4688). Publications arising from this study will be open-access. PROSPERO registration number: CRD42020172122.